2002
DOI: 10.1006/dbio.2001.0555
|View full text |Cite
|
Sign up to set email alerts
|

Follistatin Regulates Bone Morphogenetic Protein-7 (BMP-7) Activity to Stimulate Embryonic Muscle Growth

Abstract: Bone morphogenetic proteins (BMPs) can either promote growth of embryonic muscle by expanding the Pax-3-expressing muscle precursor population or restrict its development by inducing apoptosis. Follistatin, a proposed BMP antagonist, is expressed in embryonic muscle. Deficiency in Follistatin results in muscle defects and postnatal asphyxia. Here, we report that during chick limb development Follistatin enhances BMP-7 action to induce muscle growth but prevents the ability of BMP-7 to induce apoptosis and musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 44 publications
6
90
0
4
Order By: Relevance
“…1B). Follistatin is a well characterized antagonist of Activin signaling that can antagonize BMP signaling in some systems (43,44) but not others (45). To determine if the low level of Follistatin expression in ES cells modulates BMP signaling in mouse ES cells, follistatin levels were reduced via siRNA transfection, and Id1 expression was examined to measure BMP-Smad1/5 activity.…”
Section: Manipulation Of Smad7 Levels Alters Sb431542-mediated Phosphmentioning
confidence: 99%
“…1B). Follistatin is a well characterized antagonist of Activin signaling that can antagonize BMP signaling in some systems (43,44) but not others (45). To determine if the low level of Follistatin expression in ES cells modulates BMP signaling in mouse ES cells, follistatin levels were reduced via siRNA transfection, and Id1 expression was examined to measure BMP-Smad1/5 activity.…”
Section: Manipulation Of Smad7 Levels Alters Sb431542-mediated Phosphmentioning
confidence: 99%
“…These genes were also strongly expressed in C2C12 cells, but displayed only low levels in SM tissue. By compiling sets of genes that vary significantly in their mean relative expression between the two RMS subtypes (Tables 2 and 3), we detected several genes previously associated with rhabdomyosarcomagenesis or myogenic differentiation, namely Fos (Fleischmann et al, 2003), myogenic differentiation 1 (MyoD1) (Kablar et al, 2003), Junb (Chalaux et al, 1998), follistatin (Amthor et al, 2002;Armand et al, 2003), heparin binding epidermal growth factor-like growth factor (Chen et al, 1995), matrix metalloproteinase 9 (Kherif et al, 1999) and p21 cip1/waf1 (see Figure 4b). These genes generally displayed higher transcript levels in Ptch1-dependend RMS than in p53-dependend RMS (Table 2).…”
Section: Ptch1-and P53-dependent Rms Differ Extremely In the Time Of mentioning
confidence: 99%
“…Follistatin also inhibits the effects of OP-1 (also known as BMP-7), if added at a 10-fold excess (Yamashita et al, 1995). During the development of chick limbs, follistatin promotes the ability of BMP-7 to induce muscle growth but inhibits the ability of BMP-7 to induce apoptosis and muscle loss by flexible and reversible binding to BMP-7 (Amthor et al, 2002). Iemura et al (1998) demonstrated that in the early Xenopus embryo follistatin can inhibit the effects of BMP-2, -4 and -7 by direct binding to a complex of BMP and its receptor.…”
Section: Function Of Follistatin As a Binding Proteinmentioning
confidence: 99%